Natural metabolites used in traditional Chinese medicine for cardiovascular diseases: pharmacological mechanisms, evidence, and future directions - Liu, Xinyu; Zhang, Wenfeng; Miao, Xiao; Hu, Yinghua (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of death and disability worldwide, highlighting an urgent need for new treatments. Traditional Chinese Medicine (TCM) offers a rich repository of natural metabolites (flavonoids, alkaloids, saponins, etc.) that act on multiple targets to protect the heart and blood vessels. These compounds have demonstrated multiple cardioprotective effects, including anti-inflammatory, antioxidant, anti-atherosclerotic, and blood pressure–lowering activities. They work by reducing oxidative stress, dampening chronic inflammation, improving blood vessel function, correcting abnormal lipid levels, and mitigating cardiac fibrosis. Recent preclinical studies and clinical trials show that TCM-derived metabolites can improve cardiovascular health. For instance, the multi-herb formula Qili Qiangxin and the alkaloid berberine have improved heart failure symptoms and cardiac function in clinical trials when added to standard therapy. These examples underscore the clinical potential of TCM compounds. However, challenges like poor bioavailability, complex multi-component interactions, and lack of standardization still hinder their widespread use. To address these issues, researchers are exploring advanced drug delivery methods and better quality control with modern analytical tools. If these hurdles are overcome, TCM-derived therapies could be successfully integrated into mainstream cardiovascular care, offering a novel multi-target approach to combat CVDs.